STRATEGI PEMASARAN BAWANG MERAH DALAM MENINGKATKAN PENDAPATAN PETANI DI DESA OEHANDI, KECAMATAN ROTE BARAT DAYA, KABUPATEN ROTE NDAO - Nelin Afita Adu; Charles Kapioru; Santhy Chamdra (Yayasan Panca Bakti Wiyata Pangandaran, 2026)
Marketing plays a significant role in determining the success of shallot farming because it directly affects farmers' income. Shallot farmers in Oehandi Village face several challenges, including unstable market prices, limited market access, weak digital promotion, and inadequate packaging practices that reduce product value. This study aims to analyze the internal and external factors affecting shallot marketing and formulate appropriate marketing strategies to improve farmers' income. The research was conducted in Oehandi Village, Southwest Rote District, Rote Ndao Regency using a survey method. Respondents consisted of 40 shallot farmers and 6 traders selected through purposive and saturated sampling techniques. Data were collected through observation, interviews, questionnaires, and documentation. The analysis employed Internal Factor Analysis Summary (IFAS), External Factor Analysis Summary (EFAS), and SWOT analysis. The results indicate that the main strengths include high-quality products, suitable agro-climatic conditions, competitive prices, and the initial adoption of social media for promotion. The main weaknesses are limited capital, inadequate storage facilities, low utilization of digital technology, and short product shelf life. Opportunities include increasing market demand, digital marketing development, processed product diversification, and higher prices during supply shortages. Meanwhile, threats consist of price fluctuations, climate change, increasing competition, and limited market access. SWOT analysis places the business in Quadrant I, indicating a growth-oriented strategy. Recommended strategies include improving product quality, strengthening farmer institutions, expanding digital marketing, developing value-added products, and broadening market networks. These strategies are expected to enhance competitiveness and sustainably increase farmers' income.